Kajian persepsi penerapan elemen merentas kurikulum kreativiti di dalam pengajaran dan pembelajaran tulisan jawi - Wan Marzuki, Wan Ismail (2021)
The Cross-Curricular Elements (EMKs) are elements of value added that need to be instilled into the teaching and learning (T&L) process, which is included in the Primary School Standard Curriculum (KSSR). These elements were added into the curriculum aiming to enhance students’ skills and aptitude in preparing them for the current and future challenges. There are 10 elements outlined in the curriculum and one of them is the element of creativity and innovation. This survey study aims to identify the perceptions of Islamic education teachers (GPI) on creativity and its applications in teaching and learning (T&L) in Jawi classes. This is because GPI implements the application of creativity in the PdP of Jawi writing without clearly understanding the meaning of creativity as outlined in the KSSR. A clear understanding is important to help teachers plan and design a more creative and effective T&L and at the same time encourage students to get interested in Jawi and able to think creatively. Respondents were the GPI teachers in the Kuantan district area. A total of 120 respondents were randomly selected to answer the questionnaire, and from this, 30 respondents were further randomly selected to be interviewed. The objectives of the study were to i) identify teachers’ perceptions on the enhancement of creativity in the teaching and learning of Jawi, ii) examine teachers’ perceptions of their level of understanding on the enhancement of creativity in the teaching and learning of Jawi, iii) examine the teachers’ creativity knowledge and skills in the teaching and learning of Jawi, and iv) explore the influences of moderating variables on the teachers’ perceptions. This study employed a mixed method design consisting of quantitative and qualitative methods. The instruments used were questionnaires and interview methods. Quantitative data was analyzed descriptively and inferentially using Statistical Package for Social Sciences (SPSS) software, and the content analysis technique using thematic analysis was used to analyse the qualitative data obtained through the interview sessions. The overall results showed that teachers have very good perceptions on creativity based on the mean values obtained. The teachers’ understanding on the application of the EMK creativity also indicated high means. However, the mean value of the respondents’ selfassessment of the creativity shows moderate mean values. Generally, findings of the interview data indicated that the teachers have positive perceptions of creativity in teaching and learning, as well as their understanding on the application of the EMK creativity in the teaching and learning of Jawi. However, the analysis for their level of understanding on the application of EMK creativity in the T&L of Jawi in terms of knowledge and skills is moderate. As a conclusion, GPI's perception of the application of creativity elements in Jawi subject is good. Although Jawi is not a core subject like other subjects in primary school, GPIs are aware that the applicati on should be implemented not just of its clear emphasis in the Kurikulum KSSR but also but also helps students to master in Jawi and in the mean time, it cultivates a culture of creative thinking and encourage students to think creatively